2009
DOI: 10.1097/inf.0b013e3181ba6c92
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Extended Viral Resistance in Human Immunodeficiency Virus-1-Infected Mozambican Children After First-Line Treatment Failure

Abstract: Residual viral replication in children receiving stavudine/zidovudine + lamivudine + nevirapine treatment is associated with a time-dependent risk of acquiring cross-resistance, including resistance to drugs currently used for second-line treatment and also to the new generation of non nucleoside reverse transcriptase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
5
16
0
Order By: Relevance
“…31,32 Although there was a limited number of inclusions in the present series of children receiving a second-or third-line regimen, the rate of virological success was very low, with only 27% of children exhibiting an undetectable plasma viral load. In contrast, virological failure and NRTI-or NNRTIresistance mutations (even after excluding the M184V mutation) were much greater in children under a second-/ third-line treatment than in those under a first-line regimen.…”
Section: Discussionmentioning
confidence: 76%
“…31,32 Although there was a limited number of inclusions in the present series of children receiving a second-or third-line regimen, the rate of virological success was very low, with only 27% of children exhibiting an undetectable plasma viral load. In contrast, virological failure and NRTI-or NNRTIresistance mutations (even after excluding the M184V mutation) were much greater in children under a second-/ third-line treatment than in those under a first-line regimen.…”
Section: Discussionmentioning
confidence: 76%
“…[9] Finally, several studies have reported on the outcome of antiretroviral treatment in children in Africa, but only a few reports are available on long-term outcomes and in adolescents. [19,2325,35,37,39,40] …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, specific resistance mutations have been described for non-B subtype viruses. In particular, the child harbouring a C subtype, who was initially treated in Mozambique with suboptimal control of HIV-1 replication because of limited access to antiretrovirals [10], did not respond to etravirine. The recently described E138A mutation, along with an accumulation of baseline resistance mutations observed in our patient, might have compromised susceptibility to etravirine in patients with non-B subtypes [11].…”
Section: Betweenmentioning
confidence: 99%